2017
DOI: 10.1371/journal.pone.0188558
|View full text |Cite
|
Sign up to set email alerts
|

Parenting style and family type, but not child temperament, are associated with television viewing time in children at two years of age

Abstract: ObjectivesDespite the American Academy of Pediatrics (AAP) recommending that electronic media be avoided in children under two years of age, screen use is common in infants and toddlers. The aims of this study were to determine how parenting style, infant temperament, and family type are associated with television viewing in two-year-old children. Study designParticipants were from the Prevention of Overweight in Infancy (POI) randomized controlled trial (n = 802) (Dunedin, New Zealand). Demographic informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 54 publications
3
48
0
Order By: Relevance
“…On the other hand, children with more screen time in the early years of life were associated with negative parenting, including relaxed and strict parenting, but were inversely related to nurturing parenting in the subsequent year. Our findings on associations between screen time and different patterns of parenting styles support previous studies . However, parenting styles were not related to television viewing with and without computer or tablet use in toddlers, preschool and school‐aged children in some studies .…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…On the other hand, children with more screen time in the early years of life were associated with negative parenting, including relaxed and strict parenting, but were inversely related to nurturing parenting in the subsequent year. Our findings on associations between screen time and different patterns of parenting styles support previous studies . However, parenting styles were not related to television viewing with and without computer or tablet use in toddlers, preschool and school‐aged children in some studies .…”
Section: Discussionmentioning
confidence: 63%
“…Our findings on associations between screen time and different patterns of parenting styles support previous studies . However, parenting styles were not related to television viewing with and without computer or tablet use in toddlers, preschool and school‐aged children in some studies . Such contradictions between studies could plausibly be due to differences in many factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So preschoolers' screen-using behavior needs specific attention and deep observation. In addition, there were still lots of factors affecting the amount of time children spent on screen, like parenting style and family type (Howe et al, 2017). Besides, another study has shown that parental screen time were positively associated with children's screen time (Lauricella, Wartella, & Rideout, 2015).…”
Section: Introductionmentioning
confidence: 99%